Assembling the Austrasian Letters at Trier and Lorsch. Issue 1 (19th January 2016) - Barrett, Graham; Woudhuysen, George
Abstract : This article is a reconsideration of the Epistulae Austrasicae . We critique the widespread notion that the constituent letters were compiled by a courtier in the late sixth century at Metz as a book of models for use in the Austrasian chancellery. We argue instead that a monk from the monastery of Lorsch assembled the letters in the early ninth century from individual exemplars and groupings that he found in archives at Trier. We conclude by outlining some implications of this rereading for the edition and interpretation of the letters as sources for the Merovingian period, and point out some avenues for future research on their reception in the Carolingian period.